1997
DOI: 10.1111/j.1530-0277.1997.tb03724.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Prenatal Ethanol Administration in a Reciprocal Cross of C57BL/6J and Short‐Sleep Mice: Maternal Effects and Nonmaternal Factors

Abstract: An animal model was used to see if maternal genetic factors contribute to ethanol-induced fetal malformations. Susceptible C57BL/6J (B6) and resistant Short-Sleep (SS) mice were used in a reciprocal cross-breeding design. This design produced four fetal genotypes: true-bred B6B6 and SSSS liters and hybrid B6SS and SSB6 litters. Dams were intubated with either 5.8 g/kg of ethanol or an isocaloric amount of maltose-dextrin on day 9 of pregnancy. Fetuses were removed on day 18 of pregnancy and assessed for soft t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…These distinctions were observed for the hybrid, genetically similar progeny, consistent with maternal genetic factors contributing to susceptibility. Gilliam et al 23 had similar findings, except that fetal, not maternal, genotype conferred susceptibility to fetal weight deficits. Gilliam and Irtenkauf 22 and Gilliam et al 23 found that ethanol-exposed progeny with different genotypes that were carried by the same maternal strain showed distinct rates of malformation, indicating that fetal genotype also plays a role in susceptibility.…”
Section: Disease: Fetal Alcohol Syndromementioning
confidence: 75%
See 2 more Smart Citations
“…These distinctions were observed for the hybrid, genetically similar progeny, consistent with maternal genetic factors contributing to susceptibility. Gilliam et al 23 had similar findings, except that fetal, not maternal, genotype conferred susceptibility to fetal weight deficits. Gilliam and Irtenkauf 22 and Gilliam et al 23 found that ethanol-exposed progeny with different genotypes that were carried by the same maternal strain showed distinct rates of malformation, indicating that fetal genotype also plays a role in susceptibility.…”
Section: Disease: Fetal Alcohol Syndromementioning
confidence: 75%
“…Gilliam et al 23 had similar findings, except that fetal, not maternal, genotype conferred susceptibility to fetal weight deficits. Gilliam and Irtenkauf 22 and Gilliam et al 23 found that ethanol-exposed progeny with different genotypes that were carried by the same maternal strain showed distinct rates of malformation, indicating that fetal genotype also plays a role in susceptibility. However, in both cases, the effect was only significant when progeny were carried by the more susceptible maternal strain, indicating that maternal genotype had a greater influence than fetal genotype on susceptibility to ethanol teratogenesis.…”
Section: Disease: Fetal Alcohol Syndromementioning
confidence: 75%
See 1 more Smart Citation
“…Animal models, particularly mice, have proven to be an invaluable resource for investigating genetic influences on many phenotypes, including several prenatal alcohol traits. Both inbred and selectively bred mice can differ in susceptibility to many of the detrimental effects of in utero ethanol exposure, which provides additional support for the importance of genetics in the development of FASD (Boehm et al, 1997; Downing et al, 2009; Giknis et al, 1980; Gilliam et al, 1989, 1997; Webster et al, 1980). …”
Section: Introductionmentioning
confidence: 96%
“…Allelic differences in alcohol dehydrogenases affect maternal blood alcohol levels, the dose that reaches the embryo, and thus FAS risk (Chernoff, 1980;Giknis et al, 1980;McCarver et al, 1997). Gilliam and colleagues documented mouse strains that exhibit distinct ethanol-induced dysmorphologies in response to equivalent maternal blood alcohol levels and exposure windows; they reported differential sensitivities to limb and urogenital defects, learning deficits, postnatal growth, and brain reductions (Boehm et al, 1997;Gilliam and Kotch, 1996;Gilliam et al, 1987Gilliam et al, , 1997Goodlett et al, 1989). Chick strains also exhibit differential sensitivity with respect to mortality, growth, cardiac deficits, and ethanol-induced cell death (Becker and Shibley, 1998;Bruyere and Stith, 1993;Debelak and Smith, 2000).…”
Section: Genetic Background Influences Facial Outcomementioning
confidence: 92%